Measurement and disclosure for investments in associates in the Iraqi environment and international accounting standards (A comparative study) - اسيل عطية عبيد النعيمي; خولة حسين حمدان (Journal of Madenat Alelem University College, 2018)
The Measurement and Accounting disclosure requirements for investments in associates in the Iraqi environment differ from international accounting standards, Accounting recognition under local accounting rules requires conditions and events that differ from those required by international standards, The adoption of international accounting standards leads to the possibility of comparison between the financial statements of companies and to serve many parties, including investors in making their investment decisions, The research aims to identify what investments in associates are in accounting thinking and identify deficiencies in the measurement and disclosure of investments in associates under local accounting rules and the consolidated accounting system by comparing it with IAS, The study presented a set of recommendations, the most important of which is the need for the Iraqi Accounting and Auditing Standards Board to issue a local accounting rule to regulate the accounting treatment of investments in associates based on IAS 28, taking into account the Iraqi environment.